EMPLOYMENT GENERATION FROM RURAL TOURSIM: A FIELD STUDY OF THE LOCAL COMMUNITY AT KUMBALANGI IN KERALA - Manoj P. K.
Tourism is recognized as a sector with immense potential economic development and employment generation. Therefore, the governments promote it the word over, particularly in developing nations like India. As per international agencies like World Tourism Organization (WTO), it is estimated that nations like India and China would become the superpowers in the global tourism map by the year 2020. However, in spite of the excellent tourism resources in India, the country could not utilize its vast potential, because only during the last two decades it has been getting due attention. In respect of Kerala state in particular – one of the states with the highest tourism resources in India – the situation is more chronic as Kerala‟s performance in tourism has not at all been commensurate with its enviable tourism resources. In the above context, this paper makes an empirical study of the employment generated from rural tourism based on a field study of the local community at „Kumbalangi‟ – a rural tourism destination in Ernakulam district in central Kerala and the first model tourism village in India